IMPLEMENTATION GAP IN PUBLIC-PRIVATE PARTNERSHIP (PPP) FOR INFRASTRUCTURE DEVELOPMENT - K., Andriansyah Tiawarman; Sara, Rineke (International Journal of Social Service and Research, 2024)
Infrastructure is one of the most important pillars in the development of a civilization, especially for archipelagic countries like Indonesia, which faces unique geographical challenges. The gap in the implementation of Government and Business Entity Cooperation (KPBU) in infrastructure development in Indonesia has become an increasingly pressing issue to address. This research discusses the importance of regulatory renewal in Public-Private Partnerships (PPP) to address existing gaps. The research utilized various data sources, including legislative texts, government regulations, legal documents, and policy papers relevant to PPP in Indonesia. The analytical approach allowed for a deeper exploration of the dynamics and implications of the existing regulations, focusing on their effectiveness and applicability in real-world scenarios. The author was able to articulate the challenges faced in the application of PPP regulations and propose targeted recommendations for regulatory renewal and improvement. This study could involve comparative analyses of best practices in regulatory frameworks from other countries that have successfully addressed similar infrastructure challenges, providing valuable insights for the Indonesian context. Ultimately, this research could contribute to creating a more responsive and adaptive regulatory framework that supports sustainable and equitable infrastructure solutions in Indonesia, ensuring that the needs of society are met while fostering a conducive environment for investment.